Informação e Critério de Relevância:podem as máquinas aprender a diferenciar contextos? - Rodrigues, Mariana Vitti [UNESP]; Gonzalez, Maria Eunice Quilici [UNESP] (My University, 2011)
The aim of this paper is to investigate the notion of criteria of relevance with the help of the concept of information characterized by Charles Sanders Peirce. For criteria of relevance we mean a process of choosing the best action in a context. To this end, we will introduce questions relating to the study of mind, especially those concerning the debate between mechanism X non-mechanism. In an attempt to shed light on issues concerning the nature of mind, we introduce the characterization, proposed by Peirce, the concept of information. Differentiating the concept of genuine information and of degenerate information, arguing that the detection of genuine information allows to characterize the relevant actions in a given context. Initially, we will organize our work questioning whether a machine can have autonomous criteria of relevance, that is, if it can learn different criteria formulated by your programmer. Investigating whether an artificial being can learn to differentiate between contexts and therefore act in the best possible way on each occasion. Finally, we will make an balance of Peirce's contributions to this theme.

O objetivo deste artigo é investigar a noção de critério de relevância com o auxílio do conceito de informação tal como caracterizado por Charles Sanders Peirce. Por critério de relevância entendemos um processo de escolha da melhor ação em um dado contexto. Para tanto, introduziremos questões relativas ao estudo da mente, em especial aquelas referentes ao debate mecanicismo X não mecanicismo. Numa tentativa de lançar luz sobre a problemática referente à natureza da mente, introduziremos a caracterização, proposta por Peirce, do conceito de informação. Diferenciaremos o conceito de informação genuína de informação degenerada, argumentando que a detecção de informação genuína possibilita cxaracterizar as ações relevantes em um dado contexto. Organizaremos nosso trabalho inicialmente questionando se uma máquina pode ter critério de relevância autônomo, isto é, se ela pode adquirir critérios diferentes daquele formulado por seu programador. Investigando se um ser artificial é capaz de aprender a diferenciar contextos e consequentemente agir da melhor maneira possível em cada ocasião. Por fim, faremos um balanço das possíveis contribuições de Peirce para o tema em questão.